(untitled) (Fiep Bulletin - online, 2025)
Introduction: The psychological aspects of football referees are key to their overall performance on the field and have a major influence on the progress of the match. These aspects are well-known and generate the need for research on the subject. Objective: The objective is to investigate and delve into various factors related to the psychological conditions and effects that football referees may be subject to in a match, and to understand how they could influence decision-making, as well as to assess the psychological perceptions that referees have about their activity. Methodology: The research used a qualitative exploratory methodology in the form of a digital (online) questionnaire to obtain the desired data. A sample of 14 referees of different age groups and genders answered 16 questions, whose answers related to the topic were classified by percentage. This data was collected between December 2021 and January 2022. Results: External and highly emotional issues do in fact influence the decision-making of a refereeing professional. Although it is not possible to generalize that anxiety is caused by external judgment and by fans, it is possible to understand that there is fear and a feeling of guilt arising from the impossibility of a referee making a mistake. The research reveals the existence of such factors in the professional field of a referee. The multidisciplinary field of physical education and psychology are knowledge aggregators and seek to achieve results in health and sports.